A Nonpediatric Extraosseous Ewing Sarcoma of the Pancreas: Differential Diagnosis and Therapeutic Strategies - Binoy Yohannan; Mark Feldman (Case Reports in Oncological Medicine)
Extraosseous Ewing’s sarcoma is a rare and aggressive malignant tumor with a poor prognosis. The pancreas is an extremely uncommon primary site, with only 27 cases that have been published worldwide. We report a 26-year-old female who presented with 5 days of left upper quadrant pain, nausea, and vomiting. On examination, she was anicteric and had epigastric and left upper quadrant tenderness without guarding, rebound tenderness, or a palpable mass. She had slightly elevated serum aminotransferase and lipase levels. Abdominal computerized tomography revealed a multilobulated tumor arising from the body and tail of the pancreas. A biopsy confirmed a small round cell tumor, and immunohistochemistry was positive for CD99 in approximately 70% of the tumor cells. A fluorescence in situ hybridization (FISH) assay showed a 22q12 rearrangement. She was diagnosed with extraosseous Ewing sarcoma of the pancreas and underwent multiagent neoadjuvant chemotherapy followed by surgical resection, but subsequent imaging revealed evidence of systemic disease progression. She chose to go on hospice care and died a few weeks later.